Стили противоборства в современной вольной борьбе - Латышев, С.; Latyshev, S. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
На основе анализа данных литературы и соревновательной деятельности борцов высокого класса выявлены и обоснованы семь стилей противоборства. Установлена взаимосвязь доминирующих физических качеств и особенностей телосложения, формирующих стиль противоборства борца вольного стиля On the basis of the analysis of theoretic materials and high class wrestlers' competition activity seven styles of fighting are exposed. The interrelation between predominant wrestler's physical features and peculiarities of his constitution were determined as factors forming sportsmen' fighting style.
The Style of Fighting in Modern Freestyle Wrestling
Keywords: борьба; соревнования; стиль противоборства; чемпион; wrestling; competition; style of fighting; champion